(3GdcGaj aj GdaQGFVs - (3CHh YHO Gddg ESMGb Hf jhSa Hf jYbhH Hf EHQGgje GdUQOaj GdTGaYj,J (B500 (3g` s
(3ChdgG (B:s
(3ChdI (B: (3cJGH GdaQGFV (B: (3GdMeO ddg eejJ GdCfaS heYjOgG , hhGQK GdCQVjf heHJOFgG CMeOg Ydi eG hgH ef GdYdhe s
(3BNQgG (B:s
(3hef GdKef CQHYI hNeShf eY GdPi ai CjOjge ef GdYHO , hGdKef jchf CQHYI hNeSjf hgh eKdG GdhUjJjf Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdg Jedjc bOjes
(3cJHJ GdYfGhjjf HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs